The association between car accident fatalities and children's fears: A study in seven EU countries. - Viviane Kovess-Masfety; David Sowa; Katherine Keyes; Mathilde Husky; Christophe Fermanian; Adina Bitfoi; Mauro Giovanni Carta; Ceren Koç; Dietmar Goelitz; Sigita Lesinskiene; Zlatka Mihova; Roy Otten; et al. (PLoS ONE)
Children's fear of a car accident occurring to parents or themselves has been used as a concrete example to illustrate one of the symptoms of anxiety disorders such as separation anxiety and generalized anxiety. However, its usage across countries may be questionable where the prevalence of this specific type of injury differs. This cross-sectional study compares samples from seven diverse European countries (Bulgaria, Germany, Italy, Lithuania, Netherlands, Romania, Turkey) to see if an environmental exposure, car accident death rate per 100,000 people (country-wide from WHO data), is associated with children's self-report of car accident fears. In this study, 6-11 year-old children were surveyed by a diagnostic instrument (Dominic Interactive) about several situations and asked if they believed they were similar to a fictional child depicted in said situations. Mothers were surveyed for additional sociodemographic information. Multivariable logistic regression was used to adjust for covariates including mother's age, mother's education, single parenting, and mother's professional inactivity. We report a monotonic relationship between higher car accident death rates and the prevalence of children reporting fear of parent's or own accident. Relative to a reference of 3.9 deaths per 100,000 people, children's odds of reporting fear of parent's accident ranged from 1.99 (95% CI 1.51-2.61) times to 4.84 (95% CI 3.68-6.37) times as the risk of death by car accident increased across countries. A similar result arose from fear of child's own accident, with significant ORs ranging from 1.91 (95% CI 1.53-2.40) to 2.68 (95% CI 2.07-3.47) alongside increased death rates. Given that reporting of these fears accompanies correspondingly high accident death rates, the pertinence of using fear of car accidents as an illustration for some diagnostic item for mental disorders cross-nationally appears to be an issue.